(untitled) (Nepal Medical College Journal, 2022)
Calot’s triangle is an anatomical space and also known as “triangle of cholecystectomy”. It is bounded medially by Common hepatic duct, laterally by cystic duct, and superiorly by the under surface of liver and its main contain is Cystic artery. The variation in the origin and course of the cystic artery can cause serious problems resulting, severe arterial bleeding during any surgical procedures. Hence, variations in the Calot’s triangle are very important for the surgeons. An observational cross sectional study was carried out in Department of Anatomy of two Medical Colleges in Kathmandu, Nepal. A total of 30 embalmed human cadavers were dissected, in 27 cases (90.0%), cystic artery arose from right hepatic arteries, the mean length was 11.47 mm. One (3.3%) cystic artery arose from proper hepatic artery, one (3.3%) from superior mesenteric artery and one (3.3%) from accessory hepatic artery and the length of the cystic arteries were found to be measured as 15.88 mm, 27.49 mm and 24.17 mm respectively. The cystic artery was also found to be lying inside and outside the Calot‘s triangle in 96.7% and 3.3% respectively. In 26 cases (86.7%) cystic arteries were observed as passing posterior to the common hepatic duct. Further in 2 cases (6.7%) cystic arteries were found to be lying anterior to the common hepatic duct. Result also showed as in 1 case (3.3%) it was running anterior to the bile duct and in 1 case (3.3%) between right and left hepatic ducts. In conclusion the variations in the origin and course of the cystic artery are essential in performing cholecystectomy (open or laparoscopic).